Intensified Total Neoadjuvant Therapy in Patients With Locally Advanced Rectal Cancer: A Phase II Trial. Issue 12 (December 2021) - De Felice, F.; D'Ambrosio, G.; Iafrate, F.; Gelibter, A.; Magliocca, F.M.; Musio, D.; Caponetto, S.; Casella, G.; Clementi, I.; Picchetto, A.; Sirgiovani, G.; Parisi, M.; et al.
Abstract: Aims: We assessed the efficacy and safety of total neoadjuvant therapy, including targeted agent plus FOLFOXIRI (5-fluorouracil, leucovorin, oxaliplatin and irinotecan) induction chemotherapy followed by intensified chemoradiotherapy (CRT) and surgical resection, in patients with locally advanced rectal cancer. Materials and methods: This was a single-arm, single-centre phase II trial. Eligible patients had non-metastatic locally advanced rectal adenocarcinoma. Based on Ras-BRAF status, patients were treated with bevacizumab (mutated Ras-BRAF) or panitumumab/cetuximab (wild-type Ras-BRAF) plus FOLFOXIRI regimen followed by oxaliplatin–5-fluorouracil-based CRT and surgery. The primary end point was pathological complete response rate. Secondary end points were toxicity, compliance, tumour downstaging, complete resection, surgical complications, local and distant failures and overall survival. The sample size was planned to expect an absolute 20% improvement in pathological complete response rate over historical literature data with an α error of 0.05 and a power of 80%. Results: Between October 2015 and September 2019, 28 patients (median age 66 years) were enrolled. All patients had regional lymph node involvement at diagnosis. FOLFOXIRI plus bevacizumab was administered in 11 mutated Ras-BRAF patients, whereas the 17 wild-type Ras-BRAF patients received FOLFOXIRI plus panitumumab/cetuximab. Overall, total neoadjuvant therapy was well tolerated and 26 patients (92.9%) completed the programmed strategy. A complete response was achieved in nine cases (32.1%) and a nearly pathological complete response (ypT1 ypN0) in two patients (7.2%). There was no evidence of febrile neutropenia and no grade 4 adverse events were recorded. Radical resection was achieved in all cases. Conclusion: FOLFOXIRI plus targeted agent-based induction chemotherapy and intensified CRT before surgery showed promising clinical activity and was well tolerated in locally advanced rectal cancer patients. This phase II trial provides a strong rationale for phase III studies.